2014
DOI: 10.1148/radiol.13130982
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Hemodynamic Impairment: Assessment with Resting-State Functional MR Imaging

Abstract: Resting-state functional MR imaging temporal-shift analysis can noninvasively demonstrate the extent and degree of perfusion delay in patients with hypoperfusion both with and without neurologic deficit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
91
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(101 citation statements)
references
References 17 publications
6
91
0
4
Order By: Relevance
“…20,21 Some of the earliest studies on BOLD delay found spatial similarities between MTT lesions and BOLD delay lesions. 7,8 Our study shows that BOLD delay is related to both Tmax and MTT on a quantitative level. Although Tmax is the major predictor of BOLD delay, MTT predicts BOLD delay to some extent even when the influence of Tmax is adjusted for (Table 1).…”
Section: Discussionmentioning
confidence: 64%
“…20,21 Some of the earliest studies on BOLD delay found spatial similarities between MTT lesions and BOLD delay lesions. 7,8 Our study shows that BOLD delay is related to both Tmax and MTT on a quantitative level. Although Tmax is the major predictor of BOLD delay, MTT predicts BOLD delay to some extent even when the influence of Tmax is adjusted for (Table 1).…”
Section: Discussionmentioning
confidence: 64%
“…Intact brain regions had altered temporal hemodynamic flow, which either led or lagged behind the mean time course of intact grey matter. This finding was replicated in the acute and chronic stages of stroke, and steno-occlusive vessels disease (Amemiya et al, 2014; Siegel et al, 2016). Hemodynamic changes could emerge for at least two possible reasons.…”
Section: Introductionmentioning
confidence: 63%
“…Recently, rs-fMRI data were used to identify temporal hemodynamic changes in post-stroke populations (and proved crucial for understanding the true basis of altered FC) (Amemiya et al, 2014; Lv et al, 2013; Siegel et al, 2016). Intact brain regions had altered temporal hemodynamic flow, which either led or lagged behind the mean time course of intact grey matter.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further effort to obtain the signal component that is most relevant to CO 2 fluctuation was undertaken by identifying the frequency band (0.02–0.04 Hz) that shows the higher correlation with end-tidal CO 2 . A few studies have also been reported to use resting-state fMRI data to estimate blood transit time in the brain (Amemiya et al, 2014; Christen et al, 2015; Tong and Frederick, 2014). We have tried to obtain the voxel-wise delay following a previous study (Christen et al, 2015) and apply it in resting-state CVR mapping.…”
Section: Discussionmentioning
confidence: 99%